Familial synpolydactyly with variable expressivity in two siblings: a case report and review of literature - V. S., Sri Hari Ram; Chathriwala, Burhannuddin; Sheth, Binoti; Rathod, Aravind; Shetty, Rajath; Soni, Harshil; Gedam, Abhijit (International Journal of Research in Orthopaedics, 2026)
Synpolydactyly (SPD), classified as syndactyly type II, is a rare congenital anomaly characterized by central digit syndactyly with associated digital duplication. Most nonsyndromic SPD cases arise from HOXD13 polyalanine repeat expansions, which demonstrate variable expressivity and incomplete penetrance. This case report describes two biological male siblings with congenital limb anomalies. Detailed clinical examination, radiographic analysis, developmental assessment, and family evaluation were conducted. A literature review was performed to contextualize the phenotypic variability of HOXD13-associated SPD. The elder sibling demonstrated complex polysyndactyly of both hands and feet, including postaxial polydactyly and hypoplastic accessory digits. The younger sibling exhibited milder features consisting of syndactyly and polydactyly of the hands and unilateral partial toe syndactyly. Both parents had normal limb examinations, supporting reduced penetrance, a known feature of HOXD13-associated SPD. These cases highlight the considerable intrafamilial phenotypic variability characteristic of HOXD13-related SPD. Recognition of reduced penetrance is essential for accurate counseling and recurrence-risk assessment. Early diagnosis permits timely surgical planning and referral for genetic counseling.